Cambodia : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
Despite the global slowdown, Cambodia's economy has been holding up, driven by resilient exports and tourism and a strong real estate recovery. Fiscal policy has remained anchored in rebuilding government deposits and maintaining long-term fiscal debt sustainability, while providing adequate financing for Cambodia's vast development needs. Executive Directors identified greater mobilization of fiscal revenues imperative to rebuild government deposits, and maintained that focus should be on measures that would generate substantial additional revenue and create strong positive externalities.